Pengenalan Vertical Garden Dengan Augmented Reality Untuk Siswa Sekolah Menengah Atas - Djamain, Yasni; Cahyaningtyas, Rizqia; Luqman; Sikumbang, Hengki; Sangadji, Iriansyah BM; Hidayawanti, Ranti (TERANG, 2024)
ABSTRACT Community service activities carried out by the PLN Institute of Technology on the Introduction to Vertical Garden with Augmented Reality. This activity aims to teach students about the concept of vertical gardens and introduce Augmented Reality (AR) technology to optimize the learning experience for students. The activity employs an interactive approach by combining the concept of vertical gardens with AR technology. Students can access more information about each type of plant by pointing the AR device at the plants. This provides an interactive and enjoyable learning experience for students. Through this activity, it is hoped that students can develop awareness of the importance of environmental conservation and apply the concept of gardens. By introducing the concept of vertical gardens and AR technology to high school students, the PLN Institute of Technology hopes to help create a generation that cares about the environment and can apply students’ knowledge in sustainability and nature preservation efforts. Keywords: multimedia, vertical, plant cultivation, Augmented Reality (AR), Vertical Garden ABSTRAK Kegiatan pengabdian masyarakat yang dilakukan oleh Institut Teknologi PLN tentang Pengenalan Vertical Garden dengan Augmented Realit. Kegiatan ini bertujuan untuk mengajarkan siswa tentang konsep taman vertikal dan memperkenalkan teknologi Augmented Reality (AR) dalam mengoptimalkan pengalaman belajar para siswa. Kegiatan ini menggunakan pendekatan interaktif dengan menggabungkan konsep taman vertikal dengan teknologi AR. Para siswa dapat mengakses informasi yang lebih dalam tentang setiap jenis tanaman dengan mengarahkan perangkat AR ke tanaman tersebut. Hal ini memberikan pengalaman belajar yang interaktif dan menyenangkan bagi siswa. Melalui kegiatan ini, siswa diharapkan dapat mengembangkan kesadaran akan pentingnya menjaga lingkungan dan dapat menerapkan konsep taman. Dengan memperkenalkan konsep taman vertikal dan teknologi AR kepada siswa sekolah menengah, Institut Teknologi PLN berharap dapat membantu menciptakan generasi yang peduli terhadap lingkungan dan mampu mengaplikasikan pengetahuan para siswa dalam upaya keberlanjutan dan pelestarian alam. Kata Kunci: multimedia, vertical, budi daya tanaman, Augmented Reality (AR), Vertical Garden